Simultaneous transcranial and transcutaneous spinal direct current stimulation to enhance athletic performance outcome in experienced boxers - Ali-Mohammad Kamali (Nature Portfolio, 2021)
Abstract Transcranial direct current stimulation (tDCS) is among the rapidly growing experimental approaches to enhance athletic performance. Likewise, novel investigations have recently addressed the effects of transcutaneous spinal Direct Current Stimulation (tsDCS) on motor functions such as reduced reaction time. The impact of tDCS, and tsDCS might be attributed to altered spontaneous neural activity and membrane potentials of cortical and corticomotoneuronal cells, respectively. Given the paucity of empirical research in non-invasive brain stimulation in sports neuroscience, especially in boxing, the present investigation studied the effects of neuromodulation on motor and cognitive functions of professional boxers. The study sample comprised 14 experienced male boxers who received random sequential real or sham direct current stimulation over the primary motor cortex (M1) and paraspinal region (corresponding to the hand area) in two sessions with a 72-h interval. Unlike sham stimulation, real stimulation improved selective attention and reaction time of the experienced boxers [enhanced selective attention (p < 0.0003), diminished right hand (p < 0.0001) and left hand reaction time (p < 0.0006)]. Meanwhile, the intervention left no impact on the participants’ cognitive functions (p > 0.05). We demonstrated that simultaneous stimulation of the spinal cord and M1 can improve the performance of experienced boxers through neuromodulation. The present study design may be extended to examine the role of neurostimulation in other sport fields.